DESAIN PEMBELAJARAN MEMVARIASI FABEL DENGAN MENGINTEGRASIKAN PENDIDIKAN ESTETIKA - Praharwati, Dyan Wahyuning (Paramasastra: Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2016)
Curriculum is used as a foundation that contains technical rules. Curriculum used in the practice of education is currently 2013 curriculum. Language and literature Indonesia teaching should be implemented based on the national 2013 curriculum. In the 2013 curriculum KD 4.13 there are varying the fable/legend of the local area by changing the characters, setting, end of story, and serving on a secondary class VII. KD 4.13 learning especially for the text of the fable can be done by integrating the education of aesthetics. Aesthetic education strives to capture the beauty in works of literature. The aesthetics in literary works include aesthetics of language, aesthetic, cultural, aesthetic and transcendental. Integrating the education of aesthetics can be done by way of capturing such aesthetic forms in the works of literature. Aesthetics of literary works that captured can be used to perform variations against the fable. The activities of fables varying is done with structure, language, content, or genre varying. Fables varying learning can also be used to prepare the students to face the MEA. MEA is the current discourse concerning the renewal of the economic activities of the ASEAN community. Attempts to prepare the students to face the MEA can be done by way of a creative economy aiming by way of entering the field of publishing/printing as well as performances. Results of the study theory paper is focused on the discussion (1) fables varying learning, (2) the form of aesthetic value, (3) learning design of fables varying by aesthetic education integrated, and (4) the efforts of the creative economy was aiming for.